The Evaluation of Zakat Index Literatures - Irni Nuraini (Fara'id and Wealth Management, 2021)
Various measurements of the performance of zakat institutions, or the zakat index, have existed in multiple countries, with each indicator or variable used. This study aims to analyze the literature on the zakat index by covering research trends and future research directions. A total of 52 articles from Scopus with publications ranging from 1994-2022 were analyzed using the VOSViewer software. The quantitative approach is used in the bibliometric analysis, and the qualitative approach is used in the literature study. The findings in this study include research clusters divided into five groups: Zakat Performance, Zakat and Poverty Alleviation, Zakat and Human Development, Zakat Efficiency and Zakat in OIC or muslim countries.